Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
1) 3x+y=-1 5x-y=9
First of all we have add both equation but to be sure that the value we want to eliminate are both in a way that would make it possible t be deleted.
3x+y=-1
5x-y= 9
8x = 8
x= 1
In this case we are able to eliminate y becuase if we add +y-y we get that our answer is 0. and 3x + 5x would be 8x and -1+9 would be equal to 8 and to find x we needed to divided giving us that the answer for x is 1 becuase 8/8 is 1.
Then to find y we substitude the value of x in any of the formulas.
3(1)+y= -1
3+y= -1
y= -1-3
y=-4
When we have our y value we can determine if it is correct by replace the values.
5(1)--4= 9
5+4= 9
9=9
Up until now we are fine. So we do the same with the other equation.
3(1)+-4=-1
3+-4=-1
-1=-1
So by this we can now detemine that.
x= 1
y= -4
2) 4x+6y=24 4x-y=10
4x+ 6y =24
4x-y=10 (*-1)
4x+6y=24
-4x+y=-10
7y= 14
y= 14/7
y= 2
In this case we are not able to delete any of the variables so we multiplied by -1 to be able to eliminate x.
Then to find x we substitute the value of y in any of the formulas.
4x-2=10
4x= 10+2
x= 12/4
x= 3
So we now know our variables so we substituted them to see if they are correct.
4(3)+6(2)=24
12+12=24
24=24
We do the same with the other equation.
4(3)-2=10
12-2 =10
10= 10
So we can assume that.
x= 3
y= 2
3)2x-y=-3 x+3y=16
(3*)2x- y= -3
x+ 3y = 16
6x -3y = -9
x+3y =16
7x= 7
x= 1
In this case we are not able to delete any of the variables so we multiplied by 3 to be able to eliminate y.
Then to find y we substitute the value of x in any of the formulas.
1+ 3y = 16
3y= 16-1
y= 15/3
y= 5
So we now know our variables so we substituted them to see if they are correct.
2(1)- 5 =-3
2-5= -3
-3= -3
We do the same with the other equation.
1+3(5)= 16
1+15=16
16=16
So we now are sure that
x= 1
y= 5
4) 2x+3y=7 3x+4y=10
2x+3y =7 ( * - 4)
3x+4y =10 ( * 3)
-8x -12y = -28
9x +12y = 30
x= 2
In this case we are not able to delete any of the variables so we multiplied one of teh quations by - 4 to be able to subtract in our sum and the other by 3 to have the same number on y to be able to eliminate y.
Then to find y we substitute the value of x in any of the formulas.
2(2)+3y= 7
4+3y=7
3y= 7-4
y= 3/3
y= 1
So we now know our variables so we substituted them to see if they are correct.
3(2)+4(1)= 10
6+4=10
10=10
We do the same for the other
2(2)+3(1)=7
4+3= 7
7=7
So with that we can say that.
x= 2
y= 1
First of all we have add both equation but to be sure that the value we want to eliminate are both in a way that would make it possible t be deleted.
3x+y=-1
5x-y= 9
8x = 8
x= 1
In this case we are able to eliminate y becuase if we add +y-y we get that our answer is 0. and 3x + 5x would be 8x and -1+9 would be equal to 8 and to find x we needed to divided giving us that the answer for x is 1 becuase 8/8 is 1.
Then to find y we substitude the value of x in any of the formulas.
3(1)+y= -1
3+y= -1
y= -1-3
y=-4
When we have our y value we can determine if it is correct by replace the values.
5(1)--4= 9
5+4= 9
9=9
Up until now we are fine. So we do the same with the other equation.
3(1)+-4=-1
3+-4=-1
-1=-1
So by this we can now detemine that.
x= 1
y= -4
2) 4x+6y=24 4x-y=10
4x+ 6y =24
4x-y=10 (*-1)
4x+6y=24
-4x+y=-10
7y= 14
y= 14/7
y= 2
In this case we are not able to delete any of the variables so we multiplied by -1 to be able to eliminate x.
Then to find x we substitute the value of y in any of the formulas.
4x-2=10
4x= 10+2
x= 12/4
x= 3
So we now know our variables so we substituted them to see if they are correct.
4(3)+6(2)=24
12+12=24
24=24
We do the same with the other equation.
4(3)-2=10
12-2 =10
10= 10
So we can assume that.
x= 3
y= 2
3)2x-y=-3 x+3y=16
(3*)2x- y= -3
x+ 3y = 16
6x -3y = -9
x+3y =16
7x= 7
x= 1
In this case we are not able to delete any of the variables so we multiplied by 3 to be able to eliminate y.
Then to find y we substitute the value of x in any of the formulas.
1+ 3y = 16
3y= 16-1
y= 15/3
y= 5
So we now know our variables so we substituted them to see if they are correct.
2(1)- 5 =-3
2-5= -3
-3= -3
We do the same with the other equation.
1+3(5)= 16
1+15=16
16=16
So we now are sure that
x= 1
y= 5
4) 2x+3y=7 3x+4y=10
2x+3y =7 ( * - 4)
3x+4y =10 ( * 3)
-8x -12y = -28
9x +12y = 30
x= 2
In this case we are not able to delete any of the variables so we multiplied one of teh quations by - 4 to be able to subtract in our sum and the other by 3 to have the same number on y to be able to eliminate y.
Then to find y we substitute the value of x in any of the formulas.
2(2)+3y= 7
4+3y=7
3y= 7-4
y= 3/3
y= 1
So we now know our variables so we substituted them to see if they are correct.
3(2)+4(1)= 10
6+4=10
10=10
We do the same for the other
2(2)+3(1)=7
4+3= 7
7=7
So with that we can say that.
x= 2
y= 1
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.